Specialized trauma care in the acute period of trauma for a victim with unstable pelvic ring injury and acute acetabulum fracture - I. V. Kazhanov; A. K. Dulaev; S. I. Mikityuk; G. M. Besaev; V. G. Bagdasaryanz; M. A. Andreeva; I. M. Samokhvalov (Вестник хирургии имени И.И. Грекова)
The final reconstructive treatment of complex pelvic injury in a patient with combined trauma in the acute period of traumatic disease is presented. Indirect reposition, limited access, stable functional osteosynthesis were performed, which allowed to obtain a good anatomical and functional outcome.